In situ garnet Lu-Hf geochronological data (second measurement) of the Wutai-Fuping crustal section - Jia-Hui Liu; Jonas Kaempf; Meiyun Huang; Nicolas Riel; Jinghui Guo; Guangyu Huang; Lin Chen; Shujuan Jiao; Mengxia Mao; Chris Clark; Juan Wang; Qian W L Zhang; et al. (PANGAEA, 2025)
We measured garnet Lu-Hf isotope using a RESOlution 193 nm excimer laser-ablation (LA) system connected to an Agilent 8900 QQQ ICP-MS at the John de Laeter Centre (JdLC) at Curtin University, Australia. The measurement was performed in 2024 July. We present 176Lu/176Hf and 177Hf/176Hf ratios, etc.
In: Liu, J-H et al. (2025): Mineral and bulk compositions measured by EPMA, geochronological data measured by LA-ICP-MS and SIMS, for the Wutai-Fuping crustal section [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974551